Effect of leukapheresis on pain reduction in leukemic priapism - Shahida Noushad; Dibyajyoti Sahoo; Abhishekh Basavarajegowda; Esha Toora; Purshotam Paudel (Asian Journal of Transfusion Science, 2022)
Priapism is a rare presentation of Chronic Myeloid Leukaemia (CML). It is also considered a medical emergency as delay in treatment may lead to impotence. Prompt medical and surgical interventions such as hydroxyurea, analgesia, phenylephrine injection and aspiration, open surgical shunting, and local radiation therapy are essential. Leukapheresis effectively reduces leukocyte count rapidly and effectively, thereby an important therapy along with other standard of care in CML-induced priapism. In the present case, priapism was the presenting symptom of CML. The same was managed with various modalities such as hydroxyurea, allopurinol, antibiotics, analgesics, sedatives, phenylephrine injection, and aspiration but failed to reduce priapism pain. With a single cycle of leukapheresis, priapism pain could be reduced significantly.